APLIKASI PENGENALAN ANATOMI SISTEM PENCERNAAN PADA TUBUH MANUSIA MENGGUNAKAN TEKNOLOGI AUGMENTED REALITY - Ratna Meilinda; Dewi Sartika; Nazori Suhandi (Informatics Engineering, Faculty of Computer Science, 2023)
Natural Sciences (IPA) is a science related to human endeavors in understanding and finding out about the universe through precise observations and using procedures that can be explained by reasoning so as to get a clear conclusion. There are 5 main branches in Natural Sciences, namely Astronomy, Biology, Chemistry, Earth Sciences, and Physics. Science learning should be able to provide direct experience so as to increase the ability to understand and apply the concepts that have been learned. Anatomy is a branch of biology that deals with the structure of living things, in the anatomy of the human body, there are organs that support the formation of the body as a whole. The organs of the body such as bones, joints, skeletal muscles, brain, digestive system, and circulatory system and other organs. The digestive system is a process of mechanically and chemically breaking food into a form that is easier for the body to absorb. interactively in real time. The existence of technology in the form of Augmented Reality will facilitate the process of introducing information and displaying Anatomy Learning objects. This research aims to introduce anatomy to a digestive system in the human body using Augmented Reality technology which can facilitate students in the learning process. The software development method used to design and implement traditional musical instrument recognition applications is the Rational Unified Process method. Application testing is carried out using black-box testing and user testing. User testing was carried out by distributing questionnaires at SMP Negeri 2 Pedamaran Timur. Testing user satisfaction is calculated using a Likert scale and the results of questionnaire questions which can have a final score of 87% which is included in the strongly agree category